Perspectives in the Prevention and Control of Non- Communicable Diseases (NCD) - Rahman, Md Ridwanur; Yunus, Emran Bin; Faiz, MA (Journal of Bangladesh College of Physicians and Surgeons, 2010)
DOI: 10.3329/jbcps.v27i2.4247 J Bangladesh Coll Phys Surg 2009; 27: 59-62